Factors That Influence The Provision Of Complete Basic Immunization In Jambi - Nelly Sulis Tilawati; M. Ridwan; Asparian, Asparian (International Journal of Health Engineering and Technology, 2023)
Child health problems are one of the important prospects that must be considered by a country. One of the factors that can cause health problems in children is disease transmission. This problem can be prevented by carrying out complete basic immunization activities for infants and toddlers. This study aims to determine what factors are related to the provision of basic immunization to infants in the working area of ​​the Putri Ayu Health Center, Jambi. This research method is quantitative research with a cross sectional approach. The sampling technique used was multistage cluster sampling and obtained 84 respondents. The instrument used by the child is a questionnaire. The results showed that the factors related to the provision of basic immunization to infants in the working area of ​​the Putri Ayu Jambi Public Health Center were mother's education (p-value 0.001), family support (p-value 0.007) and the role of health workers (p-value 0.004). In addition, the mother's occupation and mother's knowledge did not have a significant relationship. The conclusion of this study is that there is a relationship between giving basic immunization to infants in the working area of ​​the Putri Ayu Jambi Public Health Center, namely education, family support and the role of health workers.